A redução e a relevação da sanção no Direito Tributário pelo Regulamento do ICMS do Estado de São Paulo (DECRETO Nº 45.490/00) - Peres Júnior, José Orivaldo (2017)
This paper will address the article 527-A of the ICMS Regulation in the State of São Paulo, in which, regulates the article 92 of the Ordinary Law of São Paulo nº 6.374/89, establishes requirement to the reduction or relevance of the tax penalties according to the tributary legislation. Regarding solely to the article 527-A of the ICMS Regulation in the State of São Paulo (State Enactment nº 45.490/00 – RICMS/00), due to the request of the rule in question by the judging organs in the majority of their decisions, each one of the tenets will be examined, focusing on a clearer comprehension of the purview of the applicability of the semi-open permissive rule in the tributary sanction in the legislation of the State of São Paulo, without losing track on the jurisprudence of Tax Supreme the Law. It is our concern the way the administrative jurisdictional acts in São Paulo have been conducted in measuring the tributary sanctions, because the legal demands and criteria are not always accurately observed. Administrative penalties are illegally kept, either by their precariousness of justifications or by their lack of fundamentalism, without any adjustment, or even reduced or forgiven. The judging organ in charge has the power and the task to apply the article 527-A, when the legal requirements are present, underlying adequately in the measurement of the tributary sanction, considering all the criteria the rule forecasts. Highlighting that the measurement of the tax penalty implies not only in the reduction or remission of the tax penalty fixed by the fiscal authority giving the tributary credit, but also in its own maintenance, according to the circumstances of the concrete case, which is inherent to the individualization of the penalties. Thus, the administrative jurisdictional decision, no matter what, must be based adequately on the constitutional law and principles in vigor, subject to the penalty of nullity. This exegesis is applied equally to the Judiciary Power, which has currently been dealing with the measurement of the tributary sanctions, having in most of the cases, wrong interpretations of the tributary rules that regulate the subject without defined criteria whose jurisprudential evolution is still timid. Whereas, the main legal aspects of the legal system of tax penalties and the necessary observance of the explicit and implicit constitutional principles, which permeate the Sanction Tributary Law, and consequently are applied relentlessly when having the incidence of the rule 527-A of the State Enactment nº 45.490/00. Among the principles of the Judiciary, there is the applicability of the non confiscation to tax penalties, depending on iterative case law of the Supreme Court jurisprudence, as well as the principles of reasonability, proportionality, equality and individualization of the sanctions, regarding the tax penalty. Without seizure, it will be investigated whether the Judiciary may, by decision of the Judiciary based on the Supreme Law, build one or more criteria of the main rule of the tributary incidence, focusing on the remission of the fiscal fine for equality, aiming the Principle of the Legislative, Judiciary and Executive Independence, according to the article 2º of the Supreme Law. And, justly because of this judicial activism that this dissertation also aims at deep thinking about the need of juridical rules which establish requirement and criteria to the fiscal authority, consisting of the tributary credit, the administrative judge, in the full scope of the Contentious Administrative Tributary, and the Judiciary, be able to establish the tributary penalty, focusing on the circumstances of the concrete case, chiefly to attribute juridical safety to the “taxpayer”. In this report, methodological cut of this study will be done aiming at a deep approach of the article 527-A of the Regulation of the ICMS in the State of São Paulo (State Enactment nº 45.490/00), whose significance is undeniable in the Tax Law, even though is it little dealt with by the doctrine. The gradation competence to the tax penalty has been granted just for the judging organs of the Contentious Administrative Tributary, according to the article 527 –A of the Regulation of the ICMS in the State of São Paulo (State Enactment nº 45.490/00), in which the approach of the main aspects of the administrative tributary process Bandeirante shows itself to be propitious to be highlighted, indeed, it will be weighed the suitability or not of the remission or relevance of the fiscal fine as expressed in the final part of the article 1 of the Law nº 13.457/09. Finally, the limits of the revision will be debated so the Judiciary Power is able to review in pejus the tributary sanction fixed in the Contentious Administrative Tributary, by the impossibility of discussion of the Tributary Administration own acts. Thus, an answer to the reader is intended to be given, which consists in presenting a correct appliance of the article 527-A of the State Enactment nº 45.490/00, taking to account the objective requirements and criteria of the subjective incidents, in order to have the measurement of the tributary sanction